2021
DOI: 10.1038/s41598-021-84563-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental and core temperature on cyclooxygenase and PGE2 in healthy humans

Abstract: Whether cyclooxygenase (COX)/prostaglandin E2 (PGE2) thermoregulatory pathways, observed in rodents, present in humans? Participants (n = 9) were exposed to three environments; cold (20 °C), thermoneutral (30 °C) and hot (40 °C) for 120 min. Core (Tc)/skin temperature and thermal perception were recorded every 15 min, with COX/PGE2 concentrations determined at baseline, 60 and 120 min. Linear mixed models identified differences between and within subjects/conditions. Random coefficient models determined relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…One unexpected finding was that Del exposure upregulates cox2 expression while suppressing the production of PGG2. We speculated that the unstable prostaglandin intermediary PGG2 is highly unstable in the brain and then rapidly transformed into PGH2 via specific enzymatic activities 40 . Overall, our results suggested that the metabolic pathway for arachidonic acid was dysregulated after chronic Del exposure.…”
Section: Discussionmentioning
confidence: 66%
“…One unexpected finding was that Del exposure upregulates cox2 expression while suppressing the production of PGG2. We speculated that the unstable prostaglandin intermediary PGG2 is highly unstable in the brain and then rapidly transformed into PGH2 via specific enzymatic activities 40 . Overall, our results suggested that the metabolic pathway for arachidonic acid was dysregulated after chronic Del exposure.…”
Section: Discussionmentioning
confidence: 66%
“…Orexin serves a number of functions, including regulating sleep and wake states, feeding behaviour, reward systems, mood and cognition [ 24 ], with evidence from animal studies indicating that orexin is also implicated in the regulation of body temperature at rest [ 134 , 223 ] and during exercise [ 123 ]. However, whilst the findings of Shin et al [ 198 ] are promising, it has been noted that this study did not adjust for the plasma volume changes occurring with HA and should therefore be interpreted cautiously [ 43 ]. Moreover, they are based on a limited sample size ( n = 9), and an atypical HA regime consisting of 10 bouts of 30-min hot water immersion over a 3-week period, as well as deep and mean body temperature calculation from tympanic measurement which is of questionable validity (e.g.…”
Section: Candidate Biomarkersmentioning
confidence: 94%
“…Although the role of energy homeostasis in thermoregulation is well accepted [ 200 ], it has mainly been studied within the context of exposure to cold, and in the control of the production of additional heat via the influence of hypothalamic-pituitary-thyroid axis on the metabolic processes that constitute facultative (non-shivering) thermogenesis [ 195 ]. Similarly, the role of the prostaglandin–cyclooxygenase system is well established in febrile temperature regulation [ 86 ] and has recently received some attention in the context of exposure to cold [ 43 , 50 ]. However, there is some evidence suggesting that these processes may also play a role in the adaptive processes to chronic heat exposure and as such may be suitable for further investigation in the context identifying a biomarker of the head adapted phenotype.…”
Section: Candidate Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation